Scoping Review: Benefits of Zingiberaceae Family in Patients With Cancer - Diah, Kusuma Ayu; Annisa, Yunia; Bahar, Yenni; Histopaedianto, Indrasto (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2024)
Traditional medicine has begun to be widely used in the treatment and prevention of disease, which is supported by the increasing prevelance of chronic diseases and failure of treatment with modern medicine. Cancer as one of the chronic diseases that causes the most death in the world has begun to change treatment patterns using traditional medicines to minimize side effects that occur, one of which is the Zingiberaceae family. This study was conducted to determine the benefits of the Zingiberaceae family in cancer patients, by reviewing published articles. Articles are searched through the Google Scholar, Pubmed and Scopus databases contained in the Publish and Perish application. The results of this study obtained three Zingiberaceae plants in 13 article that had been clinically testes on cancer patients and met the inclusion exclusion criteria for this study. The three plants are: Zingiber officinale (ginger), Curcuma longa (turmeric), and Boesenbergia rotunda (intersection of keys). Zingiber officinale (ginger) is known to have benefits for cancer patient by reducing nausea and vomiting caused by chemotherapy, while Curcuma Longa (turmeric)and Boesenbergia rotunda (cucumber) are known to reduce the degree of oral mucositis due to radiotherapy.